The Effectiveness of Project-based Learning Model to Develop Students’ Social Skills (Journal of Primary Education, 2019)
The objective of this study is to describe the use of project-based learning model to enhance students’ social skills of the fourth graders at SDN 1 Sedonglor and SDN 1 Panongan of Dewi Sartika after participating in project-based learning. This study was a classroom action research using project-based learning and adapting Kemmis and McTaggart model. The subject of this study was the fourth graders SDN 1 Sedonglor and SDN 1 Panongan of Dewi Sartika with the total of 72 students. Students’ social skills were measured based on the improvement in the percentage of students’ social skills during learning process. The research instrument used in this study was observation sheet of social skills. From the results of the study, it can be concluded that project-based learning can enhance students’ social skills of the fourth graders SDN 1 Sedonglor and SDN 1 Panongan of Dewi Sartika in the animal life cycle lesson. Students’ social skills improved from 67.91 before the treatment to 82.15 after the treatment. The results show that PjBL is effective to enhance students’ social skills.